Good and Services Tax: Filling or Emptying the Coffers? - Abraham, Ann (Journal of Management World, 2025)
Taxation is a phenomenal device available to the government to reduce the gap between rich and poor and to establish vertical equity through income redistribution. It is the most important source of revenue for conducting the developmental activities of the government. The sales tax system has been constantly undergoing reforms with the latest being the introduction of Goods and Services Tax in 2017. The Goods and Services tax reform was introduced with a major intent to improve the revenue collections of the state. Five years have now passed since the introduction of the reform. The study aims at finding out the impact of this reform on the government revenue of the state of Kerala.